Citra Merek dan Marketing Mix Terhadap Keputusan Pembelian Skincare Ms Glow Melalui Word of Mouth - Oky Agustina; Bayu Kurniawan; Roro Hawik Ervina Indiworo (Yayasan Al Ma'arif Dawuhan, 2024)
The Indonesian cosmetics industry is currently experiencing rapid growth, particularly in the beauty and skincare sectors. One of the well-known and trusted skincare brands is Ms Glow. Every company adopts strategies to maintain its market share. One of Ms Glow's strategies to retain its market share is by strengthening brand image and delivering a positive brand perception to consumers. This research aims to analyze the influence of brand image and marketing mix on purchasing decisions of Ms Glow skincare products through word of mouth (WOM) among students of the Faculty of Economics and Business at PGRI University Semarang. This study employs a quantitative design. The population includes all Management Program students in the Faculty of Economics and Business. The sample was determined using the Slovin formula, resulting in 310 respondents selected through purposive sampling. Data collection was conducted using primary data obtained through questionnaires distributed to respondents with a Likert scale. The data analysis method employed is quantitative analysis, supported by SPSS software for data processing. Tests conducted include instrument testing, classical assumption tests, and multiple linear regression analysis. The research results indicate that brand image has a positive and significant influence on purchasing decisions and word of mouth; the marketing mix does not significantly influence purchasing decisions; the marketing mix has a positive and significant influence on word of mouth; word of mouth has a positive and significant influence on purchasing decisions; and word of mouth significantly mediates the influence of brand image on purchasing decisions and the marketing mix.